Introduction: resilience and the Anthropocene: the stakes of 'renaturalising' politics. Issue 2 (4th May 2017) - Grove, Kevin; Chandler, David
Abstract: The Anthropocene marks a new geological epoch in which human activity (and specifically Western production and consumption practices) has become a geological force. It also profoundly destabilises the grounds of Western political philosophy. Visions of a dynamic earth system wholly indifferent to human survival liquefy modernity's division between nature and politics. Critical thought has only begun to scratch the surface of the Anthropocene's renaturalisation of politics. This special issue of Resilience: International Policies, Practices and Discourses explores the politics of resilience within the wider cultural and political moment of the Anthropocene. It is within the field of resilience thinking that the implications of the Anthropocene for forms of governance are beginning to be sketched out and experimental practices are undertaken. Foregrounding the Anthropocene imaginary's renaturalisation of politics enables us to consider the political possibilities of resilience from a different angle, one that is irreducible to neoliberal post-political rule.